Analysis of the Vibration Modes of Impact Geoplates and Implications for Bedload Flux and Grain Size Measurements. Issue 9 (21st September 2022) - Portogallo, M.; Simoni, S.; Vignoli, G.; Bertoldi, W.
Abstract: Seismic geophones have been frequently used in combination with metal plates to indirectly estimate bedload flux in gravel bed mountain rivers. This indirect method has been calibrated with direct measurements in several conditions and proved effective to provide relevant information on spatial and temporal scales otherwise impossible to explore. Notwithstanding, a detailed description of the vibration modes of the plate is still lacking, limiting the possibility to interpret the signal. Here, we report on two sets of experiments where we explored the geoplate response in terms of frequency and amplitude of different vibrational modes. A first set of dry experiments was designed to investigate the variability of the signal as a function of the impact location on the plate. A second set reproduced standard flow conditions, with single pebbles transported by the flow. Results highlighted the occurrence of two main vibration modes, with a first rapid phase (about 5 ms) characterized by higher frequencies, and a second longer and more stable phase of vibration with a frequency in the range of 300–400 Hz. The signal of single impacts showed a good correlation with pebble mass, with only the number of impacts on the plate depending on the flow conditions. The evaluation of the grain size is a challenge given the variability of the signal generated by similar impacts. We propose a filtering strategy to improve grain size estimation. Our analysis shows that a more detailed understanding of the vibrational modes helps identifying best practices for an improved signal acquisition and elaboration. Plain Language Summary: Vibration produced by sediments transported on the riverbed can be used to indirectly estimate sediment flux in rivers. A commonly used method involves the installation of metal plates on the riverbed. Their vibration is measured by geophones and converted into metrics related to sediment flux. In this work, we performed laboratory experiments to better understand the vibration modes of the plate, measuring the frequency and amplitude of the different harmonics through a Fourier analysis. In a first set of experiments, we investigated the variability of the signal as a function of the hitting spot on the plate, in dry conditions. A second set reproduced standard flow conditions, with single particles transported by the flow. Results showed that the plate vibrates mainly with its natural frequency (about 350 Hz), with higher frequencies related to higher vibration modes damping very rapidly. Particles hit the plate one or more times, generating impacts with amplitudes related mainly to their mass, whereas the number of impacts also depends on the flow conditions. Filtering the impacts as a function of their vibration spectra may result in more accurate relationships between the recorded signal and sediment flux and may help designing improved signal acquisition and elaboration tools. Key Points: Fourier and wavelet analysis of the geophone signal highlights the plate vibrates with a fundamental frequency in the range of 300–400 Hz Amplitude of the fundamental mode depends on particles mass and is not affected by flow conditions, whereas the number of impacts is Amplitude of the main vibration mode is related to grain size, but also pebble shape has a significant role